2023
DOI: 10.3390/jcm12072639
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Urticaria Treatment with Omalizumab—Verification of NLR, PLR, SIRI and SII as Biomarkers and Predictors of Treatment Efficacy

Abstract: Biomarkers that are able to predict the response to omalizumab (OMA) in chronic spontaneous urticaria (CSU) are highly valued. The aim of our study was to evaluate the UAS7 (urticaria activity score assessed for 7 days), DLQI (dermatology life quality index), SII (systemic immune-inflammation index), SIRI (systemic inflammation response index), PLR (platelet/lymphocyte ratio) and NLR (neutrophil/lymphocyte ratio) in a group of 46 CSU a patients treated for 24 weeks with OMA (300 mg every 4 weeks). There were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The mean DLQI at the beginning of treatment was slightly higher than in pivotal studies that might relate to high initial severity scores [ 1 , 10 , 11 ]. Yet, in each cycle we observed a significant improvement in DLQI scores, which is in line with other research [ 1 , 10 , 11 , 14 , 15 ]. Furthermore, some patients experienced an improvement in the quality of life despite not responding fully to treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The mean DLQI at the beginning of treatment was slightly higher than in pivotal studies that might relate to high initial severity scores [ 1 , 10 , 11 ]. Yet, in each cycle we observed a significant improvement in DLQI scores, which is in line with other research [ 1 , 10 , 11 , 14 , 15 ]. Furthermore, some patients experienced an improvement in the quality of life despite not responding fully to treatment.…”
Section: Discussionsupporting
confidence: 93%
“… 28 Recent studies have explored the impact of omalizumab on platelet and inflammatory markers in patients with CU, but these have yielded inconsistent and inconclusive results. 17 , 29 , 30 In our study, we observed a notable trend of higher PLRs being associated with a higher likelihood of being a late responder to omalizumab treatment. However, PLR was not found to predict nonresponse to omalizumab.…”
Section: Discussionsupporting
confidence: 52%
“…The study found that responders exhibited significantly higher SII and SIRI levels compared to non-responders at three and six months after initiating omalizumab treatment [29]. However, a recent study failed to verify the utility of these biomarkers [31].…”
Section: White Blood Cell Count and Plateletsmentioning
confidence: 98%
“…One study [27] 1613 SIRI/SII/PLR/NLR Increase Predictive of response to omalizumab Contradictory [28] 252 (106 completed) [29] 124 [30] 143 [31] 56 [34] Review…”
Section: Eosinophil Count Decrease Predictive Of Non-response To Omal...mentioning
confidence: 99%
See 1 more Smart Citation